2014
DOI: 10.1017/cjn.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Early Pharmacological Thromboprophylaxis after Subarachnoid Hemorrhage

Abstract: Objective: The recent guidelines on management of aneurysmal subarachnoid hemorrhage (aSAH) advise pharmacological thromboprophylaxis (PTP) after aneurysm obliteration. However, no study has addressed the safety of PTP in the aSAH population. Therefore, the aim of this study was to assess the safety of early PTP after aSAH. Methods: Retrospective cohort of aSAH patients admitted between January 2012 and June 2013 in a single high-volume aSAH center. Traumatic SAH and perimesencephalic hemorrhage patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Aneurysm, arteriovenous malformation and cavernous malformation are the most common causes of non-traumatic intracranial hemorrhages [3][4][5]. Conventional catheter angiography is the gold standard for diagnosis of vascular abnormality; however; other imaging modalities such as CTA and MRA can help to find out about vascular abnormalities [6][7][8]. Intracranial aneurysms are the most common causes of non-traumatic intracranial hemorrhage, occurring in 60%-85% of cases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysm, arteriovenous malformation and cavernous malformation are the most common causes of non-traumatic intracranial hemorrhages [3][4][5]. Conventional catheter angiography is the gold standard for diagnosis of vascular abnormality; however; other imaging modalities such as CTA and MRA can help to find out about vascular abnormalities [6][7][8]. Intracranial aneurysms are the most common causes of non-traumatic intracranial hemorrhage, occurring in 60%-85% of cases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with pSAH of unknown etiology are primarily treated conservatively [7,8,14,[25][26][27]. However, SAH complications, such as acute and chronic hydrocephalus, may occur, often requiring surgical interventions, including temporary external ventricular drainage and cerebrospinal fluid shunting.…”
Section: Discussionmentioning
confidence: 99%
“…108 In a retrospective study of 170 patients, our group showed that giving drugs to prevent venous thromboembolism (unfractionated heparin 5,000 IU subcutaneously every 12 hours or dalteparin 5,000 IU subcutaneously daily), starting within 24 hours of aneurysm treatment, could be safe. 109 Fifty-eight percent of these patients had an external ventricular drain in place. One patient developed a major cerebral hemorrhagic complication and died while on unfractionated heparin; however, the patient was also on dual antiplatelet therapy with aspirin and clopidogrel.…”
Section: Preventing Venous Thromboembolismmentioning
confidence: 99%
“…One patient developed a major cerebral hemorrhagic complication and died while on unfractionated heparin; however, the patient was also on dual antiplatelet therapy with aspirin and clopidogrel. 109 Current guidelines suggest that intermittent compression devices be applied in all patients before aneurysm treatment. Pharmacologic thromboprophylaxis with a heparinoid can be started 12 to 24 hours after aneurysm treatment.…”
Section: Preventing Venous Thromboembolismmentioning
confidence: 99%
See 1 more Smart Citation